Endovascular treatment for basilar artery occlusion: A systematic review and meta‐analysis. (12th February 2021) - Katsanos, Aristeidis H.; Safouris, Apostolos; Nikolakopoulos, Stavros; Mavridis, Dimitris; Goyal, Nitin; Psychogios, Marios N.; Magoufis, Georgios; Krogias, Christos; Catanese, Luciana; Van Adel, Brian; Raphaeli, Guy; Sarraj, Amrou; et al.
Abstract: Background and purpose: Independent randomized controlled clinical trials (RCTs) have provided robust evidence for endovascular treatment (EVT) as the standard of care treatment for acute large vessel occlusions in the anterior circulation. We examined available studies specific to posterior cerebral circulation ischemic strokes to see if any conclusions can be drawn regarding EVT options. Methods: We performed a systematic literature search to identify studies evaluating the safety and efficacy of EVT versus standard medical treatment for patients with acute basilar artery occlusion (BAO). We extracted data for outcomes of interest and presented associations between the two groups with the use of risk ratios (RRs) or odds ratios (ORs), with corresponding 95% confidence intervals (CIs). We used a random‐effects model to pool the effect estimates. Results: We identified five studies (two RCTs, three observational cohorts) including a total of 1098 patients. Patients receiving EVT had a higher risk of symptomatic intracranial hemorrhage (sICH) compared to those receiving non‐interventional medical management (RR 5.42, 95% CI 2.74–10.71). Nonsignificant trends towards modified Rankin Scale (mRS) scores 0–2 (RR 1.02, 95% CI 0.74–1.41), mRS scores 0–3 (RR = 0.97, 95% CI 0.64–1.47), overall functional improvement (OR 0.93, 95% CI 0.57–1.51), and all‐cause mortality (RR 1.03, 95% CI 0.78–1.35) at 3 months were seen. Conclusion: Although EVT increases the probability of sICH, the available data do not exclude the possibility of improved functional outcomes over standard therapy. As larger studies are challenged by the perceived lack of equipoise in this vulnerable patient population, results of ongoing RCTs are expected to provide substantial input for future meta‐analyses. Abstract : Larger studies are challenged by the perceived lack of equipoise in this vulnerable patient population. Conditional probability analysis suggests that a very small future trial would make a combined significant effect for the outcomes of (a) modified Rankin Scale score 0–3 and (b) all‐cause mortality at 3 months in a future meta‐analysis almost certain.